Alterações no transporte hidroviário em tempos de pandemia na travessia Belém-Marajó - FIEDLER, Luan Carlos Paiva (2024)
The pandemic directly affected waterway transport, with interruptions in operations, reduced travel capacity and changes in demand, requiring the reorganization of the service. Thus, this study contributed to the identification of changes in waterway transport, with the connection Belém - Porto do Camará, at Marajó Island. The data were obtained from a field survey on board and at the Belém Waterway Terminal, involving the periods: before, during and after COVID 19. As part of results obtained, were confirmed changes in behavior and perception of quality by users, which show the need for investment in the sector.